Development of transmission use of system charges scheme for Malaysia transmission network - Samsudin, Noor Azam (2007)
Presently, the trend of electricity industry is towards restructuring of electricity supply industry, as a means to increase operation efficiency and lower energy costs. Restructuring environment is referring to unbundling of electricity utilities into its basic component such as generation, transmission and distribution. One of the outstanding issues in unbundling of electricity supply industry is transmission service pricing. This project is focus on the development transmission use of system charges scheme for Malaysia transmission network in restructuring environment. This project required to identify the costs of transmission services provided by the transmission utility and evaluating the transmission assets. The several alternatives of the allocation methods that can be used to evaluate the usage of transmission services have been studied. From this study, a suitable usage allocation method is identified. This project also involved study the transmission pricing methodologies. As the result, the transmission access pricing for Malaysia transmission will classify. The transmission access pricing must be non discrimination, transparent, economically, efficiency and allow full recovery of costs. Finally, the transmission service charge percentage is allocated between customers and generators. The developed scheme is tested on the bus systems and the TNB system to evaluate its effectiveness providing a fair transmission charges to the users.